A new SERS substrate based on Zn2GeO4 nanostructures for the rapid identification of E.Coli and methylene blue. Issue 19 (1st October 2021) - Ali, Hafiz T.; Mateen, A.; Ashraf, Fouzia; Javed, Muhammad Rizwan; Ali, A.; Mahmood, K.; Zohaib, A.; Amin, N.; Ikram, S.; Yusuf, Mohammad
Abstract: We have demonstrated the fabrication of Zn2 GeO4 nanostructures based SERS substrates and their potential application for the rapid detection of different pathogens. The SERS substrates were grown by a very simple and cheap route using vacuum tube furnace. The structure and morphology of grown SERS substrates were modulated by annealing the samples at different temperatures ranging from 600 °C to 900 °C. E.Coli and MB solutions were placed on the grown SERS substrate and investigated using Micro Raman Mapping System with 633 nm Laser having power 0.75 mW with exposure time of 2s. Raman data demonstrated that SERS substrate which was annealed at 800 °C showed highest enhancement factor of 7.9 × 10 2 MB signal. Similar enhancement of Raman signal for E. coli was also observed. The strongest Raman signal of E.Coli and MB for SERS substrate which was annealed at 800 °C is due the fact this sample has nanostructure morphology which resulted in the enhancement of Raman signal. Successful identification of E. coli and MB showed the capability of Zn2 GeO4 nanostructures to be used for the detection of pathogens.